Milletlerarası Usul Hukukunda ihtiyati tedbirler : (Brüksel I Tüzüğü, UNIDROIT ilkeleri ve Türk Yargılama Hukuku çerçevesinde) - Aydemir, Deniz Defne Kırlı (My University, 2012)
In recent years, developments in international arena especially both in commercial and social matters, bring up special relations between the parties and introduce international legal disputes. To resolve the international legal disputes with common rules and to create a harmonization of decisions given by different national courts, several institutes offer contributions to create universal harmonization or unification of procedural law. Harmonization of procedural law has made much less progress. It has been impeded by the assumption that national procedural systems are too different from each other and too deeply embeded in local and political history and cultural tradition. Provisional and protective measures are a fundamental part of civil justice and they are neccessary to secure the enforcement of decisions. They are aimed at protecting rights, parties, proceedings and judgements. In essence, they are only meant to be temporary and the exact period for which they are valid and effective is defined by the court which orders the measures or in law. They can take in many forms. These measures can be found in every developed legal system. The rules concerning these measures as well as the contents and their scope are however quite different between the national laws. Harmonization or unification of procedural law including rules concerning provisional and protective measures can be distinguished in European and universal approach. Brussels I Regulation, ALI/ UNIDROIT Principles of Transnational Civil Procedure, ILA Helsinki Principles and The Draft Hague Convention on Jurisdictions and Judgements are the most important projects which introduce common Principles in terms of unification of procedural law. With the context of both these projects and international disputes, provisional and protective measures has an important part of the conflicts which are frequently happened in different types. In international cases, provisional and protective measures could be assessed by multi-dimensional perspective. At that point, there become some important aspects that take into consideration in regards to concept of measures, content and types of measures, international jurisdiction, territorial effect of the measures and recognition and enforcement of these measures. With respect to concept of provisional and protective measures, it is difficult to define. It could be express that, something less than a full judgement. Because of that reason, neither in national laws nor in projects that aimed unification and harmonization of civil procedure, it is hard to find a definition concerning these measures. The concept of meaures, generally, accepted as a relief when necessary to preserve the ability to grant effective relief by final judgement or to maintain or otherwise to regulate the status quo according the Brussels I Regulation, ALI/ UNIDROIT Principles of Transnational Civil Procedure, Helsinki Principles of International Law Institute and Hague Judgements Convention. In Brussels I Regulation, fort the concept of these measures, Regulation explicitly refers to national law instead of giving such a autonomous definition. But through the case law of European Court of Justice, it has become clear that not all measures that are seen as “provisional” and “protective” in national legal systems can be regarded for purposes of Regulation. Also, Court of Justice accepted some objective criteria in regards to these measures in accordance with it’s decision. International jurisdiction of the courts to grant provisional and protective measures is another subject that must be discuss. At that point, two jurisdiction arise for ordering measures. One of them is the court that has jurisdiction on the merits and the other one is, the court where the measure obtained and executed. In international disputes, sometimes, there need to be taken provisional and protective measures from another court instead of the court where the main proceeding takes place. So, these two proceedings could be happened in different countries. Both Brussels I Regulation, ALI/ UNIDROIT Principles and the other projects, authorizes the courts of another states for obtaining measures beside the court on the merits. But it means that, taking these measures not from an irrelevant courts. At that point, all the projects set forth a real connection link between the subject matter of measure seek and the jurisdiction of courts. That means that, the court from where the measure is obtained could enforce these measure and the subject matter of the measure to be present in the jurisdiction of the court measure ordered. Beside this basic principle, there has been lots of matters related to measures and international jurisdiction such as; general jurisdiction, special jurisdiction, prorogation of jurisdiction, exclusive jurisdiction, exorbitant jurisdiction and lis pendes. Types of these jurisdiction has an important effect on measures both in practice and in the light of doctrine. For example, exorbitant jurisdiction doesn’t accepted most of national laws and also unification projects. Because, in exorbitant jurisdiction, a court which has a very little connection link with the subject matter of dispute could have gained an authority for jurisdiction. Because of that reason, law systems do not want to accept this kind of jurisdiction. But in Brussels I Regulation, especially for provisional and protective measures, this kind of jurisdiction accepted because of the reference that made to national jurisdiction rules. Another subject that must be mentioned is applicable law to provisional and protective mesures. Legal scholars have different solutions to offer on this isssue. On one side, measures are essentially connected with the procedure, so iti is part of lex fori. On the other hand, measures must not protect disputed claims and not be more effective than than the proceeding on the merits would be able to provide. It is justified by the notion that, provisional measures must be ordered very rapidly and that in general, the court which orders them can not obtain sufficient knowledge of any foreign law which may apply. Besides, the law on provisional and protective measures is a procedural regulation of the powers of the courts. Because of that reason, most of national laws and also the projects such as Brussels I Regulation, UNIDROIT Principles and others predominantly adopted lex fori as a applicable law to provisional and protective measures. But this doesn’t mean that the foreign law can not be applied. And indeed, foreign law as a lex causae, especially on family law or in the context of protection of child, could play an important role much more than it could. In the context of an international dispute, these measures takes place wholly or partly on the territory of a State other than the one in which they were ordered. But it seems that, national laws has always been reluctant to recognise and enforce foreign decisions made for provisional and protective purposes. This negative approach has some reason. Firstly, this measures must have a provisional character so, this condition arise as a blocking effect on enforcement. Secondly, provisional and protective measures have to create a “surprise effect”, so in some situations, it could be beter to have been taken as an ex-parte. Otherwise, the defendant or the person to whom the measure ordered for could miss the subject of measure. Thirdly, the general approach concerning to provisional and protective measures is, to take measures directly from the court where they could proceed. So, with this concept, there is no need for recognition and enforcement. However, this traditional attitude seems to have been changing softly. In the context of Brussels I Regulation, provisional and protective measures are enforceable and can have a res judicata effect which prohibits any application from obtaining the same relief. In Turkish procedural law, measures which are belong to international disputes on Turkish courts aren’t regulated specially. So, national law system could be applied both national and international cases. In practice, it’s not so important that, the dispute between the parties has an international character or not. In Turkish law, especially, concerning to measures in international disputes and their temporary character, there has been experienced some dilemmas and troubles in practice, through both jurisdictional and enforcement meaning. It could be possible to take measures before or after the main proceeding. But, the Civil Procedural Code limited the jurisdiction of the court which will obtain these measures. So, the Code only gives this authority to the courts that have jurisdiction on the merits. And this execution causes violation of legal protection rights. Lex fori is also accepted as an applicable law to provisional and protective measures because of it’s procedural character. It is also accepted that, for the integrity of the proceeding and also the difficulties to finding and applying the foreign law to these measures justifiable reasons for application of lex fori. In Turkish private international law, only the decisions which have res judicata effect could be recognise and enforced. That means, a foreign judgement must be final in the sense that it brings an end to the dispute between the parties. But traditionally, provisional and protective measures do not fall into this category. So, at first sight, temporary nature of this measure prohibits it’s recognition and enforcement. But in literatue and doctrine, it is accepted that if these measures have a res judicata effect in their home country, they could be adopted as a final judgement.
Keywords: Hukuk; Özel Hukuk